Heading Toward a More Social Future? Scenarios for Social Enterprises in Germany - Engelke, Henning; Mauksch, Stefanie; Darkow, Inga-Lena; von der Gracht, Heiko (Business & society, 2014)
In recent years, the public sector in many countries has had difficulty keeping abreast of social problems due to restricted financial resources and limited organizational capacities. As a consequence, entrepreneurs have started to address social welfare issues that the public sector has been unable to tackle with an innovative approach called social enterprise. The authors present research on the future prospects of social enterprise as a sustainable business model for industrialized countries. As there is a lack of historical and current data, the authors aim to contribute to and structure the debate about the potential of the concept. Therefore, the authors provide initial data from a Delphi survey on the future development of social enterprise in a multistakeholder environment. Experts from academia, business, nongovernmental and governmental organizations, social enterprise investors, and social entrepreneurs evaluated 16 projections for the year 2030. Based on these results, the authors present comprehensive scenarios of four different possible developments of the future of social enterprise in Germany.